Greening Global Value Chains : Some Implementation Challenges - Sinclair-Desgagné, Bernard (World Bank, Washington, DC, 2014)
The paper aims to highlight some of the most important implementation issues associated with the greening of global value chains with special attention given to how public policies and business strategies can support each other in meeting the challenge, particularly in developing countries. This requires a systemic view of global value chains that includes downstream supply chains and explicitly takes into account the relationships between regular members (raw materials providers, component manufacturers, and assembly plants, notably) and their clean-tech suppliers. It also involves a careful description of the business landscapes of global value chains as well as reliable environmental metrics and data, carefully examining how these can be shared among global value chain members and their stakeholders. Certain incentives must be set within member firms and throughout the supply chain and this involves reviewing managerial practices -- monitoring and auditing of environmental performance, compensation and rewards, transfer prices, task design and allocation, decision making processes, employee selection and training, and organizational culture -- and framing outsourcing contracts appropriately. To be effective, however, these initiatives need to be encouraged by credible national policies (which include environmental but also social policies targeting informal businesses) and international agreements, revealing disclosure programs, and a vigilant civil society. On a global level, the coordination of business and public policies is crucial as the greening of a global value chain will certainly work best if its members and stakeholders move in tandem.